PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX - Sari, Lidiya Puspita (Departemen Matematika, 2023)
Problem solving is a skill that students need to master. In fact, this ability for class IX students of SMP Negeri 28 Padang is still low. The solution provided is to apply the inquiry learning model. The purpose of the research is to examine whether the problem solving abilities of students implementing the inquiry learning model are effective compared to implementing the direct learning model in class IX of SMP 28 Padang and to identify how the problem solving abilities of students develop using the inquiry learning model. The type is quasy experimental with a non-equivalent posttest only control group design. The population is class IX students of SMP Negeri 28 Padang, class IX. 8 and IX.9 as sample classes. Quizzes and final tests in the form of essays as instruments. Reasoning in the fact investigation with the t-test, Pvalue = 0,000 was obtained. Because Pvalue <0,05 then reject H0. This demonstrates students' mathematical problem-solving abilities using an efficient inquiry learning model rather than applying a direct learning model in class IX at SMP Negeri 28 Padang. Keywords- Inquiry, Problem solving, Direct Learning, Mathematic